A Bibliometric Analysis of the Literature on Open Access in Scopus - Chung, Jenny; Tsay, Ming-Yueh (Qualitative and Quantitative Methods in Libraries; Vol 4 No 4 (2015): December 2015 Issue, 2017)
Using bibliometric techniques, this study investigates the characteristics of the literature on open access related research. The bibliometric data collected from Scopus, such as document type, country of publication, language of publication, subject area and the publication year of the open access documents, is used. In addition, the most cited articles, the top journals, the most productive authors and the institutions with the highest number of papers are also identified. The results of the study show that: 1.thirteen document types and 7,721 documents from 1972 to 2012, peer-reviewed journal articles (4,793; 62%) are the most frequently used type and the most popular publication media; 2.the US (2,204; 27%) and the UK (1,172; 14%) with 3,376 (41%) of the articles, are the countries with the greatest contribution, from a total of 128 countries’ authors; 3.English (7,316; 94%) dominates the other languages as the most frequently used language; 4.the top 3 subject areas are medicine ( 2,753; 22％), social science (1,787; 14%), biochemistry and genetics, molecular biology (1,253; 10％); 5.the last 10 years (20032012) account for 6513 (84.3%), as the highest output; 6.the most cited papers, published on Remote Sensing of Environment, are cited 2043 times, written by 13 coauthors in 1998 and supported by NASA in the US; 7.Plos One, with the most total publications on open access, published 554 papers; 8.the top 3 most productive authors are Bjork, B.C., from Finland, with 29 articles on open access, McGrath, M., from the United Kingdom, with 27articles on open access and Harnad, S., from Canada, with 24articles; and 9.the top institution is the University of Toronto (Canada). The future development of open access research will be of increasing importance, with more subject areas, authors, institutions and journals. The OA movement, an innovation in scholarly communication, is growing quickly and will widely influence in different subject areas and changes in related research worldwide.